The Effect of Personality Characteristics of Students on Positive Perception Level: A Study to Hockey Super League Players - Veysel, Temel; Kazim, Nas (Asian Journal of Education and Training, 2019)
The study was done in order to determine the effect of personality characteristics of students female athletes who participated in Hockey Super League competitions organized in Konya Province between the 15th and the 28th of April, 2018 upon their positive perception level. The study was consisted of 116 students female athletes who participated in hockey super league competitions (Average age= 18.21±2.98). In order to determine students athletes’ personality levels; “Eysenck Personality Inventory” designed by Francis et al. (1992) and “Positive Perception Scale” adapted by Akın and Kaya (2015) for the Turkish language were used. For the analyses of the data; histogram technique was employed in order to find whether or not data followed a normal distribution and as a result, it was identified that all sub-dimensions of mental endurance and positive perception scale followed a normal distribution. Accordingly, t test and One-Way-Anova tests were employed in order to explore basic differences and Canonical Correlation analyses were performed in order to find the effect between personality and positive perception levels. As a result; it was concluded that athletes demonstrated moderate level of personality and positive perception. It was seen that there was a moderate and significant correlation between sub-dimensions of Eysenck personality inventory and positive perception scale.